Socio-environmental diagnosis environmental for management plans: environmental perception of the surrounding population of the Parque Municipal da Grota Funda - Machado, Aline Ribeiro; Souza, Caroline Almeida; Silva, Marcella Fortes Falcão da; Diatchuk, Talita Teles (Revista Hipótese, 2016)
The environmental perception of the surrounding community of the Parque Municipal da Grota Funda was analysed in this study, via semi-structured interview, generating results through content analysis that supported the development of the Management Plan. This indicated priority actions to enable the surrounding occupation compatibility with the protected area conservation and was essential to define priority actions in its Management Plan.
Keywords: environmental planning; participatory planning; Municipal Park